Post-retrieval Distortions of Self-Referential Negative Memory: Valence Consistency Enhances Gist-Directed False, While Non-negative Interference Generates More Intrusive Updates - Pan, Dong-Ni; Li, Xuebing (Frontiers in Psychology, 2021)
According to the theory of reconsolidation, the contents of an original memory can be updated after reactivation with subsequent new learnings. However, there seems to be a lack of appropriate behavioral paradigm to study the reconsolidation of explicit self-related memory, which is of great significance to further explore its cognitive neural mechanism in the future. In two separate experiments, we adapted a trial-by-trial interfering paradigm with self-episodic simulation process, and investigated whether 1) it is possible to reconsolidate negative memories under the new behavioral paradigm, and 2) how the emotional valence of post-retrieval interference material affects the reconsolidation of negative memory. Our results showed that negative memories under trial-by-trial self-simulation can be degraded and updated via post-retrieval interference processes. Individuals whose original memories were reactivated by initial background cues and who were then presented with new interference situations were less able to recall original scenes and showed more memory intrusions on these scenes than those who had experienced new learning without reactivation or only reactivation without interference. Furthermore, the extent and manner of memory change/updating was greatly influenced by the characteristics of the interference information. For memories with negative valences, new learning materials with the same valence produced superior interference effects in the form of lower correct recalls and more integrated false. Whereas, the neutral interference materials can cause more memory intrusion. Post-retrieval memory distortions of negative self-memory may underlie different functional mechanisms.